Independent Work Peculiarities in the Process of Foreign Language Study in Blended Learning Environment While Training Young Specialists for the State Corporation «Rosatom» - Zakharova, L. V.; Bunames, N. V.; Zarochintseva, I. V.; Lupinogina, Yu. A.; Melkikh, M. A. (Глобальная ядерная безопасность, 2022)
The article deals with the problems of foreign language independent work in technical high schools when training specialists for State Corporation «Rosatom» in conditions of mixed education, basic principles and methods of training using electronic systems, analyzes typical mistakes, current and final control.